Apakah Likuiditas, Leverage, dan Ukuran Perusahaan Mempengaruhi Nilai Perusahaan? Bukti Empiris pada Sektor Perbankan di BEI: Do Liquidity, Leverage, and Firm Size Affect Firm Value? Empirical Evidence from the Banking Sector on the IDX - Sena Apriyani; Abid Djazuli; Ummi Kalsum (Jurnal Aplikasi Manajemen dan Bisnis, 2025)
This study aims to examine the effect of liquidity, leverage, and firm size on firm value in the banking sector listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Firm value is considered one of the key indicators for investors in assessing a company’s performance and prospects. The research population consists of 47 banks, of which 35 were selected as samples using a purposive sampling method based on specific criteria. Data were obtained from annual financial statements and analyzed using multiple linear regression. The results show that liquidity, leverage, and firm size simultaneously have a significant effect on firm value. Partially, leverage and firm size have a significant effect, while liquidity does not significantly affect firm value. These findings highlight that maintaining a sound capital structure and ensuring sustainable asset growth are key factors in enhancing firm value in the banking sector. From a theoretical perspective, this study contributes to the literature on the determinants of firm value, particularly in the Indonesian banking industry, by emphasizing the critical role of leverage and firm size as major determinants. From a practical standpoint, the findings provide useful insights for bank management in designing optimal capital structure strategies, strengthening quality asset growth, and maintaining liquidity efficiency to attract investors. For investors, these results serve as a guideline to pay closer attention to leverage ratios and firm size before making investment decisions, as both are proven to contribute to fluctuations in market value.